Regulating Digital Privacy and Surveillance in Ukraine: Legal Gaps and Harmonization with EU Standards in the Age of Big Data - Demydova, Liudmyla; Serohin, Vitalii; Yaroshevska, Tamara; Tumalavičius, Vladas; Hordiyuk, Serhii (International Journal of Law and Society, 2026)
The article examines the key legal principles for ensuring the right to digital privacy in Ukraine within the framework of the Law of Ukraine “On Digital Content and Digital Services”. The purpose of the study is to: 1) identify the legal provisions and limitations of this Law regarding the right to digital privacy; 2) indicate the challenges and opportunities in the field of ensuring digital privacy; 3) assess the compliance of Ukrainian regulation with international standards; 4) develop recommendations for strengthening legal mechanisms; 5) contribute to the achievement of Sustainable Development Goal No. 16. The research methodology involves the use of a qualitative case study, which includes document analysis and 14  interviews with experts. The data were thematically analyzed using NVivo. The results indicated that the Law regulates civil-legal relations between providers and consumers of digital services, but does not contain adequate guarantees against data misuse and third-party surveillance. Challenges include unclear terminology, lack of effective control mechanisms. Opportunities lie in bringing the legislation closer to the GDPR and implementing the “privacy by design” principle. The proposed recommendations consist of strengthening liability for violations, limiting data exchange, legally enshrining anonymity, and innovation-oriented reforms in accordance with international standards. The study contributes to the achievement of SDG 16 by developing transparent and rights-based institutions. Limitations relate to the qualitative nature of the sample and the analysis of national acts. The scientific novelty lies in the systematic combination of Ukrainian digital privacy regulation with international standards and sustainable development goals.